2010
DOI: 10.1002/pbc.22506
|View full text |Cite
|
Sign up to set email alerts
|

Is the updated Schwartz formula appropriate for assessing renal function prior to hematopoietic stem cell transplantation?

Abstract: Assessing renal function is an integral part of evaluating pediatric patients for hematopoietic stem cell transplantation (HSCT). The most accurate method is DTPA-Tc-(99m) GFR testing. However, it is costly and time consuming. The Schwartz formula, which was recently updated, represents an inexpensive and readily available alternative. We assessed agreement between the original and updated formula and DTPA-Tc-(99m) in 107 patients who were being evaluated for HSCT. Agreement between both formulas and DTPA-Tc-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Among our patients aged 1 to 16 years, the median and IQR of CL CR estimated by means of the original Schwartz equation (37) were similar to those observed previously by other authors in the same setting (38,39). Overall, nonlinear regression documented a good sigmoidal relationship between CL CR estimates and CL M (r 2 ϭ 0.733).…”
Section: Discussionsupporting
confidence: 70%
“…Among our patients aged 1 to 16 years, the median and IQR of CL CR estimated by means of the original Schwartz equation (37) were similar to those observed previously by other authors in the same setting (38,39). Overall, nonlinear regression documented a good sigmoidal relationship between CL CR estimates and CL M (r 2 ϭ 0.733).…”
Section: Discussionsupporting
confidence: 70%
“…Although nuclear GFR remains the "gold standard" for renal assessment in patients after HSCT, it is expensive, invasive, and requires exposure to radiation, necessitating the evaluation of alternative measures, such as cystatin C-based GFR. 62,63 Finally, long-term screening for proteinuria in patients with a history of TA-TMA may identify those at greatest risk of CKD and associated complications and "open the door" for the initiation of ACEI therapy. 36,86 It is important to acknowledge that the renal and cardiovascular sequelae of CKD and TA-TMA contribute significantly to shortand long-term morbidity and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…13 Others have also shown that creatininebased GFR estimation is inferior to nuclear GFR before HSCT. 62 Cystatin C, a recently introduced non-muscle-based marker of kidney function measured with a single blood test, may prove to be a useful indicator of GFR in the future, but prospective data validating this approach after HSCT are unavailable. 62,63 Second, the inclusion of lactate dehydrogenase (LDH) as a diagnostic criterion presumes that all centers check this parameter on a routine basis.…”
Section: Diagnostic Challengesmentioning
confidence: 99%
See 2 more Smart Citations